Use of Sorbents to Increase Beer Foam Stability. (2nd January 2018) - Kosin, P.; Branyik, T.; Savel, J.; Ulmann, F.; Vlcek, J.
ABSTRACT: Long-lasting creamy foam is an important quality parameter for various types of beers. Foam stability depends on both foam-stabilizing and foam-damaging compounds, and lipids are considered to be the main foam-damaging compounds. The aim of this work was to validate a technologically and economically feasible method for stabilizing beer foam using sorption. Among eight materials tested for their foam stabilizing effects (activated carbon, Florisil, polytetrafluoroethylene, montmorillonite, filter sheet, steel dust, cotton, and polyethylene), three were selected for further study to verify their effects on color, bitterness, and the sensory profile of a commercial lager beer. The results showed that the foam stabilizing effect of sorbents were positively correlated with their surface areas. The most promising sorbents (activated carbon, Florisil, and polytetrafluoroethylene) were effective at low doses (50 mg/L) and short contact times (5 min), and did not affect the color, bitterness, or sensory profile of the beer. At the low dose required and the price of sorbents, their single use in combination with other process aids and subsequent filtration should be economically feasible.